VIDEO PROFILE SEBAGAI SARANA INFORMASI DAN PROMOSI STUDIO SATU PT. MEDIA TELEVISI INDONESIA ( METRO TV ) - Lusyani Sunarya; Della Nurasiah; Firmansyah Agustian (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
Technology, especially in the areas of multimedia, audiovisual and broadcasting bound by the computer technologies that play a role important enough to get the needed information. This time information and promotional media used Studio One Metro TV, only in the form of brochures and through the official website of PT. Metro TV, by relying on the information and promotional media in a sense is not enough for the show to the audience, who would want a highly effective presentation of information, accurate, and interesting to look at in terms of look and content. Information and promotion will be presented at Studio One Metro TV quite a lot, include: activities cameraman, introduction switcher tool, master control room and others. Media video profile is intended that the public interest in an information will increase. Submission of media and information campaign designed to match the shape of the video profile that combines audio and visual, which shows the entire information relating to the Studio One PT. Media Televisi Indonesia commonly called PT.METRO TV. Methodology This study uses analysis of the problem, data collection, analysis, design and media production concept (KPM) which includes: pre-production, production and post production. The right media to support information and promotion of Studio One PT. Metro TV is using a video profile, with this profile video media is expected to support some access to information that is clear, accurate, and detailed, so it can be useful and beneficial to the audience who are interested to find out information about Studio One PT. Metro TV, and video profile is expected to improve the image in Studio One PT. Metro TV.